Examination of Salmonella Prevalence in Pigs Through Rye‐Based Feeding and Coarser Feed Structure Under Field Conditions - Jens Gerrit Lindhaus; Bernd Reckels; Bussarakam Chuppava; Richard Grone; Christian Visscher; Clara Berenike Hartung (Veterinary Medicine and Science)
ABSTRACT Introduction Salmonellosis is the second most commonly occurring bacterial zoonosis in Germany. Rye in pig feeding offers new possibilities for addressing that issue due to its high content of non‐starch polysaccharides (NSPs). These are fermented in the intestinal tract to specific fermentation products, which seem to have bacteriolytic effects against Salmonella. A coarse feed structure can display synergistic effects. Methods Seven conventional pig fattening farms increased the rye content (40%–70%) while limiting the amount of fine particles (maximum of 20% ≤0.25 mm). Samples from pigs were tested for Salmonella antibodies and compared with samples from 167 farms without any changes to the feed. Results Rye‐based diets had a significant (p < 0.05) impact on Salmonella antibody (percentage optical density [OD%]) detection. In this study, it became apparent that significantly fewer positive OD% values could be detected due to the increase in rye compared to farms that did not change the feed (Farm 6 P0: 35.45 ± 36.18; P1: 15.48 ± 16.98; P2: 9.36 ± 8.17). An elimination of Salmonella could not be achieved, but especially farms with high antibody counts were able to strongly reduce those in both phases consecutively (Farm 5 P0: 35.17 ± 35.53; P1: 18.56a ± 20.96; P2: 13.38a ± 18.99). That was different on farms without adapted feeding, where an increase in Salmonella antibodies was observed (P0: 17.38 ± 22.21; P1: 20.12 ± 25.39; P2: 18.12 ± 25.44). Conclusion By increasing the proportion of rye and limiting the proportion of fine particles in the feed, Salmonella antibodies (OD% values) in meat juice and blood can be significantly reduced, especially on farms with an initially high incidence of Salmonella. If that is implemented in feeding across the board on farms, an improvement in food safety and a decreased risk of zoonosis can be expected.